2012
DOI: 10.3354/meps09933
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low-intensity noise exposure affects the hearing thresholds of juvenile snapper

Abstract: A growing body of evidence suggests that larval fish use sound as an orientation cue to remotely locate suitable settlement habitats. Several theoretical models have used hearing thresholds to estimate the distance at which fish larvae can detect reefs. However, researchers have often measured hearing thresholds from fish raised in aquaculture environments, or held them in closed-system tanks once caught, where equipment can significantly increase the noise levels in the tanks. The possibility arises that expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…A previous study showed that fish exposed to ecotourism tend to have higher cortisol levels than fish that are protected from sound (Oliveira, Canário, & Bshary, 1999), which suggests these fish are stressed. Snapper (Caiger, Montgomery, & Radford, 2012) show a similar hearing ability to rainbow trout (Wysocki, Davidson, Smith, & Frankel, 2007), with greatest sensitivity to low‐frequency sounds (<400 Hz). Rainbow trout showed no effect of hearing loss after being exposed to sounds up to 150 dB re 1 μPa, therefore the exposure level of motorboat sound (125 dB re 1 μPa) in the present study is significantly less and unlikely to have caused any significant hearing damage to the protected fish.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that fish exposed to ecotourism tend to have higher cortisol levels than fish that are protected from sound (Oliveira, Canário, & Bshary, 1999), which suggests these fish are stressed. Snapper (Caiger, Montgomery, & Radford, 2012) show a similar hearing ability to rainbow trout (Wysocki, Davidson, Smith, & Frankel, 2007), with greatest sensitivity to low‐frequency sounds (<400 Hz). Rainbow trout showed no effect of hearing loss after being exposed to sounds up to 150 dB re 1 μPa, therefore the exposure level of motorboat sound (125 dB re 1 μPa) in the present study is significantly less and unlikely to have caused any significant hearing damage to the protected fish.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is also available that fish exposed to constant noise, such as that in aquaculture facilities, exhibit significantly higher hearing thresholds, and are acclimated to it (Caiger et al. ). In the Arctic, vessels only visit in the summer months and are not constantly present in one area.…”
Section: Discussionmentioning
confidence: 99%
“…Bluefin tuna (Thunnus thynnus) was reported to acclimate to short (10-15 s) repeating loud noise, but not to long stimuli noise (10-15 m) of the same source (associated with wind farms), or to the regular boat noise associated with feeding time (P erez-Arjona et al 2014). Evidence is also available that fish exposed to constant noise, such as that in aquaculture facilities, exhibit significantly higher hearing thresholds, and are acclimated to it (Caiger et al 2012). In the Arctic, vessels only visit in the summer months and are not constantly present in one area.…”
Section: Noise Acclimation Potentialmentioning
confidence: 99%
“…This same AEP technique has been used to begin to characterise the development of hearing over the larval life history period, initially using hāpuku (Polyprion oxygeneios), a species with an extended larval duration (Caiger et al 2013). It has also been used to show that background noise can detrimentally affect hearing thresholds (Caiger et al 2012), so care needs to taken to provide appropriate quite conditions for housing fish for later experimental evaluation of hearing thresholds.…”
Section: Hearingmentioning
confidence: 99%